Visit-to-visit HbA1c variability is associated with in-stent restenosis in patients with type 2 diabetes after percutaneous coronary intervention - Chen Die Yang; Ying Shen; Lin Lu; Zhen Kun Yang; Jian Hu; Rui Yan Zhang; Wei Feng Shen; Feng Hua Ding; Xiao Qun Wang (Cardiovascular Diabetology, 2020)
Abstract Background Patients with type 2 diabetes are under substantially higher risk of in-stent restenosis (ISR) after coronary stent implantation. We sought to investigate whether visit-to-visit HbA1c variability is a potential predictor of ISR in diabetic patients after stent implantation. Methods We consecutively enrolled type 2 diabetic patients who underwent successful elective percutaneous coronary intervention and performed follow-up coronary angiography after around 12 months. The incidence of ISR and its relationship with visit-to-visit HbA1c variability, expressed as coefficient of variation (CV), standard deviation (SD) and variability independent of the mean (VIM), were studied. Multivariable Cox proportional hazards models were constructed to analyze the predictive value of HbA1c variability for ISR. Results From September 2014 to July 2018 in Ruijin Hospital, a total of 420 diabetic patients (688 lesions) after stent implantation were included in the final analysis. During a mean follow-up of 12.8 ± 1.3 months, the incidence of ISR was 8.6%, which was significantly increased in patients with higher CV of HbA1c (P = 0.001). The mean diameter stenosis (DS), net luminal loss and net luminal gain were 22.9 ± 16.8%, 0.42 ± 0.88 mm and 1.66 ± 0.83 mm, respectively. Greater DS was observed in subjects with higher tertiles of CV of HbA1c (P < 0.001), and this trend was more prominent in patients with optimal glycemic control (HbA1c ≤ 7%) in the baseline. In multivariate analysis, HbA1c variability was independently associated with incidence of ISR after adjustment for traditional risk factors and mean HbA1c (HR: 3.00 [95% CI 1.14–7.92] for highest vs. lowest tertile). Inclusion of CV of HbA1c led to a better risk stratification accuracy. Assessing HbA1c variability by SD or VIM yielded similar findings. Conclusions This study suggests that visit-to-visit HbA1c variability is an independent predictor of incidence of ISR in patients with type 2 diabetes after stent implantation. Trial registration NCT02089360: NCT